Literature Review: Evaluation of Drug Logistics Management Implementation - Wasni Wasni; Muhammad Abdan Shadiqi; Fauzie Rahman; Rosihan Adhani; Mohammad Isa (GLOBAL HEALTH SCIENCE GROUP, 2025)
Drug logistics management is a crucial component of the healthcare system as it plays a role in ensuring the availability, quality, and accuracy of medications in healthcare facilities. Various issues such as drug shortages, procurement delays, and damaged or expired medications are still frequently encountered, necessitating a comprehensive study of the implementation of drug logistics management. This literature review aims to evaluate the implementation of drug logistics management based on previous research findings, covering planning, procurement, storage, distribution, and drug control. This study used a literature review method by searching articles through the PubMed, Science Direct, and Google Scholar databases for the period 2021–2025. An initial collection of 30,042 articles was obtained. Articles were selected based on inclusion and exclusion criteria, resulting in 10 relevant articles for analysis. The articles were reviewed using thematic analysis, grouping the findings into key themes of drug logistics management. The study indicates that most healthcare facilities have implemented drug logistics management stages, including planning, procurement, storage, distribution, and recording and reporting. However, various obstacles remain, including planning that is not fully based on actual data, procurement delays, limited storage facilities and infrastructure, and weak monitoring and evaluation systems. Human resources and training also impact the performance of drug logistics management. The implementation of drug logistics management has been ongoing, but is not yet optimal. Human resource capacity building, infrastructure improvements, the use of integrated information systems, and ongoing evaluation are needed to make drug logistics management more effective and efficient.